Mismatch between diagnostic reports and special educational needs classification in a public educational system - Maria Cristina Triguero Veloz Teixeira; Décio Brunoni; Luiz Renato Rodrigues Carreiro; Ana Claudia Braga; Naiara Adorna da Silva; Cristiane Silvestre Paula (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To assess the diagnostic status, the sociodemographic and health profiles for students with special educational needs (SEN) in a public educational system, and to map their use of educational/social services. Methods The sample comprised 1,202 SEN students from a total of 59,344 students. Results Only 792 students of the 1,202 had an established diagnosis. The most prevalent SEN condition was intellectual disability. There was a low percentage (29.4%) of use of specialized educational services or support. It was found that, for some neurodevelopmental disorders, prevalence data suggest an under-reporting in the school system. Conclusion Results suggest that there is a mismatch between the diagnostic reports and the SEN condition legally recognized according to Brazilian law, in addition to the under-reporting and under specialized service use of students with disabilities.